Gesture recognition based on the probability distribution of arm trajectories - Wan Khairunizam, Wan Ahmad, Dr.; Hideyuki, Sawada (The Society of Instrument and Control Engineers, 2012)
Link to publisher's homepage at http://www.sice.or.jp/